Important Developments of Leisure Education in American Public Schools: What Can We Learn From Them? 美國學校的休間敎育: 他山之石 - TOH, Kian Lam (Asian Journal of Physical Education & Recreation, 1999)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The notion of leisure education can trace its roots far back to Ancient Greece. The aim of leisure education is not to increase the number of subjects offered by the schools, but rather to infuse the values of leisure into the existing subjects. The objective is to guide the students in making good use of their leisure, which in fact is one of the secondary school curriculum aims. Besides presenting some of the important developments of leisure education in American public schools, this paper also highlights some of the reasons why leisure education fails in the United States. These problems are relevant to us especially if we want to make leisure education in Hong Kong a reality one day. 休閒教育的起源可追溯到古希臘時代。休閒教育的目的不在於增加學校的科目，而是將休閒的價値溶入目前學校既有的科目中，引導學生善用閒暇時間，這也正是香港的教育目標之一。美國學校的休閒教育可說是失敗的。本文首先提出休閒教育在美國的一些重要發展，然後舉出一些造成他們失敗的可能原因，若是有朝一日休閒教育在本港萌芽，那麼我們就不得不重視這些我們也可能面對的問題。